The Politics of Sex Trafficking - O'Brien, E. author. aut Link
IX, 225 p.
Keywords: This book offers a unique insight into the moral politics behind human trafficking policy in Australia and the USA, including rare interviews with key political actors, and a critical account of Congressional and Parliamentary hearings.